Faith-Based Transnational Actors and Peacebuilding: An Analysis of the Role Of Nahdlatul Ulama in Afghanistan’s Peace Process - Mahfudin, Irvan Aladip; Sundrijo, Dwi Ardhanariswari (UI Scholars Hub, 2021)
After the end of the Cold War, the idea of peacebuilding has been central to the main narrative within the study of international peace. For a significant period, the narrative was dominated by liberal and secular approaches which put state as the primary actor in peacebuilding processes. Nevertheless, many cases show that non-state actors, in particular faith-based transnational actors, might have contributed significantly to the conflict transformation mechanism through their faith-based peacebuilding activities. This article explores the modification that Rüland, von Lübke, and Baumann have made on Lederach’s concept on peacebuilding, which categorises peacebuilding processes into two dimensions: conflict evolution and crisis intervention. The first dimension of conflict evolution focuses on the identification of the root causes of the conflict and its development, while the second dimension is more concerned with the management of conflict and its transformation, as well as its impacts to the peace establishment process in certain areas. Referring to the Indonesian Nahdlatul Ulama’s involvement in the Afghanistan peacebuilding process, this article shows how the model offered by Rüland, von Lübke, and Baumann can well explain the opportunity transnational non-state actors have to contribute significantly to promote the establishment of peace in conflict areas.